A Comparative Study on Performance of Shell-and-Tube and Coil-Tube Economizer for Once-Through Boilers - ผ่องรัศมี, อุทัย; ศิริไชย, เสนีย์; อินแบน, สํารวจ (KKU Science Journal, 2014)
The research was to design and develop shell-and-tube and coil-tube economizers for once-through boiler generating steam with 250 kg/h steam producing rate at 408 kPa pressures. The measured temperature of exhaust gas boiler was 453 K entering the cross-flow economizer used to preheat the feeding water with the heating surface area and tube length of 3.55 m2 and 34 m. The research found that the economizer shell and tube exhaust with gas at 7.65 m/s produced the heat transfer coefficients of the tube outer and inner area at 33.42 and 5.71 W/m2K, respectively while the pressure drops for shell and tube were 25.69 and 2.27 Pa. The effectiveness of the economizers was 0.40 and the energy saving cost was 78,600 Baht/year. The payback period is around 2.66 years. When compared the coil tube economizer exhaust gas at 5.33 m/s, the heat transfer coefficient of the tube outer and inner area were 54.42 and 0.89 W/m2K, respectively while the pressure drops for shell and tube were 87.42 and 0.65 Pa. The effectiveness of the economizers was 0.36 and the energy saving cost was 75,300 Baht/year. The payback period is around 2.52 years. The compared shell-and-tube economizer and coil-tube economizer were suitable for once-through boilers generating steam of 500 kg/h rate at pressure steam test of 102-408 kPa.